Exposure to Community Homicide During Pregnancy and Adverse Birth Outcomes: A Within-Community Matched Design. Issue 5 (September 2019) - Goin, Dana E.; M. Gomez, Anu; Farkas, Kriszta; Zimmerman, Scott C.; Matthay, Ellicott C.; Ahern, Jennifer
Abstract : Background: Community violence is an understudied aspect of social context that may affect risk of preterm birth and small-for-gestational age (SGA). Methods: We matched California mothers with live singleton births who were exposed to a homicide in their Census tract of residence in 2007–2011 to unexposed mothers within the same tract. We estimated risk differences with a weighted linear probability model, with weights corresponding to the matched data structure. We estimated the average treatment effect on the treated of homicide exposure on the risk of preterm birth and SGA during the preconception period and first and second trimester. Results: We found a small increase in risk of SGA associated with homicide exposure in the first trimester (0.14% [95% confidence interval (CI) = −0.01%, 0.30%]), but not for exposure during the preconception period (−0.01% [95% CI = −0.17%, 0.15%]) or the second trimester (−0.06% [95% CI = −0.23%, 0.11%]). Risk of preterm birth was not affected by homicide exposure. When women were exposed to homicides during all three exposure windows, there was a larger increase in risk of SGA (1.09% [95% CI = 0.15%, 2.03%]) but not preterm birth (0.14% [95% CI = −0.74%, 1.01%]). Exposure to three or more homicides was also associated with greater risk of SGA (0.78% [95% CI = 0.15%, 1.40%]). Negative controls indicated that residual confounding by temporal patterning was unlikely. Conclusions: Homicide exposure during early pregnancy is associated with a small increased risk of SGA. Abstract : Supplemental Digital Content is available in the text.